MicroRNA-34a induces a senescence-like change via the down-regulation of SIRT1 and up-regulation of p53 protein in human esophageal squamous cancer cells with a wild-type p53 gene background. Issue 2 (28th January 2016) - Ye, Zhimin; Fang, Jun; Dai, Shujun; Wang, Yuezhen; Fu, Zhenfu; Feng, Wei; Wei, Qichun; Huang, Pintong
Highlights: Expression level of miR-34a induced by DNA damage agent adriamycin was p53- and time-dependent in ESCC. MiR-34a significantly inhibited cell growth via down-regulation of Sirtuin1 and up-regulation of P53/P21. High concentrations of miR-34a may inhibit cell growth in KYSE-410 and KYSE-450 cell lines with mutant-type p53 gene. Abstract: MiR-34a has been reported as a non-coding RNA universally expressed in normal old cells and a probable suppressor of diverse cancer cells; however, this miRNA's expression and anti-tumor mechanism in esophageal squamous cancer cells (ESCC) remains unclear. We explored these questions in three human ESCC lines, KYSE-450, KYSE-410, and ECa-109, with wild-type p53 and mutant p53 backgrounds. Through a specific stem-loop RT primer for miR-34a, we examined the relevant expression level of miR-34a in these three cell lines using real-time reverse transcription PCR (qRT-PCR). We found that the expression level of miR-34a induced by the DNA damage agent adrmycin (ADR) was both p53- and time-dependent. Following incubation with miR-34a, cellular growth inhibition was exhibited differently in the three cell lines harbored with different p53 backgrounds. Furthermore, the MTT assay demonstrated an miR-34a-related cytotoxic effect in cell growth. Senescence-associated β-galactosidase (SA-β-Gal) staining was used to examine senescence-like phenotypes induced by miR-34a. Mechanistic investigation suggested that the down-regulation of Sirtuin1 (SIRT1) and up-regulation of p53/p21 contributed to the anti-tumor mechanism of miR-34a in wild-type p53 ECa-109 cells, while neither of the apoptosis-related proteins PARP and caspase-3 caused significant changes. In summary, our findings indicated that the intrinsic expression of miR-34a was relatively low and was expressed differently among different p53 backgrounds and ADR treatment times. The anti-tumor effect of miR-34a was primarily dependent on the regulation of SIRT1 and p53/p21 protein, not apoptosis-associated proteins.